Conference program and abstracts. International Biogeography Society 6th Biennial Meeting – 9-13 January 2013, Miami, Florida, USA - Joaquín Hortal; Karen Faller; Kenneth Feeley; Richard Field; Catherine Graham; François Guilhaumon; Daniel Gavin (Frontiers of Biogeography)
Proceedings of the Sixth biennial conference of the International Biogeography Society, an international and interdisciplinary society contributing to the advancement of all studies of the geography of nature. Held at Miami, Florida, USA, 9 – 13 January 2013. Abstracts include: (i) the Opening, MacArthur & Wilson Award and Alfred Russel Award Plenary Lectures; (ii) four symposia entitled "Island Biogeography: New Syntheses", "Beyond Bergmann: New perspectives on the biogeography of traits", "The Convergence of Conservation Paleontology and Biogeography" and "Predicting species and biodiversity in a warmer world: are we doing a good job?"; (iii) oral presentations from contributed papers on Phylogeography, Marine Biogeography, Biogeography of the Anthropocene, Hot Topics in biogeography, Island Biogeography, Neotropical Biogeography, Global Change Biogeography, Historical and Paleo-biogeography, Conservation Biogeography and Global-Scale Biogeography; and (iv) contributions presented as posters on Phylogeography, Geospatial techniques and land cover, Biodiversity gradients and macroecology, Biogeography of traits, Island Biogeography, Neotropical Biogeography, Conservation Biogeography, Disturbance and Disease Biogeography, Climate Change Biogeography and Historical and Paleo-Biogeography.